ANALISIS PENGARUH PELAYANAN PENDAFTARAN TANAH TERHADAP KEPUASAN MASYARAKAT PADA KANTOR PERTANAHAN KOTA LANGSA - marlina, Marlina lubis; Nurviana (Program Studi Matematika, Fakultas Teknik, Universitas Samudra. Langsa, Aceh., 2025)
Land registration services are a form of government assistance aimed at facilitating the public in obtaining land ownership certificates. Residents of Langsa City perceive that the land registration process provides convenience and substantial benefits in managing their land certificates. However, the process of obtaining a land certificate often involves several challenges, such as incomplete documents, land disputes, complex administrative procedures, customary land issues, and other related problems.The purpose of this study is to analyze the quality of services provided by the Langsa City Land Office in relation to community satisfaction. The data used in this research are primary data obtained from questionnaires distributed to 30 respondents. The method applied is linear regression, supported by correlation coefficient tests and the coefficient of determination test.Based on the analysis, the level of community satisfaction with the performance of the Langsa City Land Office reaches 75%. Furthermore, land registration services contribute 14.2% to overall satisfaction. These findings indicate that the community of Langsa City considers the dissemination of information regarding land registration to be sufficiently satisfactory.